Evaluation of the geriatrician in the practice model of care for dementia assessment and management in rural Australia. (22nd January 2022) - Christley, Jeremy; Cuenca, Jose; Davis, Kimberley J.; Evry, Narelle; Hartwell, Tabitha; Shepherd, Karen
Abstract: Objectives: To evaluate an integrated care program expanding the physician in the practice model into geriatrics, focussing on dementia assessment and management. Design: Observational descriptive study. Setting: The rural section of a local health district in New South Wales, Australia. Participants: Patients attending eight general practices, in addition to practice nurses and general practitioners. Interventions: Self‐report questionnaires completed by patients, specialist general practitioners and practice nurses. Responses to open‐ended questions were analysed using content analysis. Routinely collected health data of patients who took part in the program were compared with data of patients from the same institution who did not take part in the program. Main outcome measures: A number of planned reviews, actual reviews and emergency department presentations for participating patients, self‐efficacy amongst general practitioners and practice nurses, and patient satisfaction and comfort levels. Results: The GIP program was well received by most patients, GPs and practice nurses. Almost 90% of patients found it easier to see the specialist at their general practice. They were less likely to have planned reviews, actual reviews and emergency department presentations than patients who did not take part in the program. GPs and practice nurses expressed increased confidence in and knowledge of dementia assessment and management. Conclusions: Dementia assessment and management programs based on the physician in the practice model may be well received in similar rural settings. Larger prospective studies are needed to further examine the relationship between programs and patients' health outcomes.